A Review on Specific Data Structures Using Data Preprocessing and Refinement of Existing Algorithms in Order to Improve Time Complexities - Hrushikesava Raju, S; Nagabhusana Rao, M (International Journal of Computer Sciences and Engineering, 2025)
The data preprocessing is helpful in removing noise, inconsistency in the given data and produce quality data. The output of the data preprocessing is then given to refinement of existing algorithm that can later applied over the data structures called external sorting, optimal binary search trees, and pattern matching algorithms. In external sorting(first case), user data entered can be qualified using Data preprocessing, then separate algorithms used to different data items such as numeric and alphabets. In Optimal binary search trees (second case), user entered data can be made quality data using data preprocessing (second case), then refined algorithm used over the data elements that produce OBSTs separately for numeric items, and String items. In pattern matching (third case), user entered data can be made quality data, then refined algorithm used over the text which immediately finds out index for the pattern along with history of indices for the substring which further helpful in manual identification of the given pattern in the large given text. The results and graphs were also demonstrated based on certain examples. This also differentiates between time complexities obtained of the existing and proposed algorithm used over the data structures such as external sorting, OBST, and pattern matching.